Applications of electron paramagnetic resonance spectroscopy to heavy main-group radicals. Issue 35 (19th August 2020) - Cutsail, George E.
Abstract : Electron paramagnetic resonance spectroscopy continues to offer powerful electronic insight into the nature of heavy main-group radical centres. Abstract : The exploration of heavy main-group radicals is rapidly expanding, for which electron paramagnetic resonance (EPR) spectroscopic characterisation plays a key role. EPR spectroscopy has the capacity to deliver information of the radical's electronic, geometric and bonding structure. Herein, foundations of electron-nuclear hyperfine analysis are detailed before reviewing more recent applications of EPR spectroscopy to As, Sb, and Bi centred radicals. Additional diverse examples of the application of EPR spectroscopy to other heavy main group radicals are highlighted.